2017
DOI: 10.1016/j.jtcvs.2017.06.040
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on functional survival in patients 1 year after cardiac surgery

Abstract: Preoperative frailty was associated with a 2- to 3.5-fold higher risk of poor functional survival 1 year after cardiac surgery. The addition of frailty to the European System for Cardiac Operative Risk Evaluation II provides incremental value in identifying patients at risk of poor functional survival 1 year postsurgery, regardless of frailty definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 36 publications
3
89
0
Order By: Relevance
“…In the current era of cardiac surgery, those aged 75 years and older represent a growing subset of patients, and the level of frailty ranges between 25% and 50% of these patients depending on the type of assessment tool used. 1,2 Successful surgical correction of cardiac disease has the potential to restore biologic function and provide substantial benefit even for older adult patients. 3,4 However, conventional cardiac surgery is associated with substantial iatrogenic stress, which can affect outcomes.…”
Section: Supplemental Materials Is Available Onlinementioning
confidence: 99%
“…In the current era of cardiac surgery, those aged 75 years and older represent a growing subset of patients, and the level of frailty ranges between 25% and 50% of these patients depending on the type of assessment tool used. 1,2 Successful surgical correction of cardiac disease has the potential to restore biologic function and provide substantial benefit even for older adult patients. 3,4 However, conventional cardiac surgery is associated with substantial iatrogenic stress, which can affect outcomes.…”
Section: Supplemental Materials Is Available Onlinementioning
confidence: 99%
“…5,6 It may be of greater interest to understand the effect of anaortic OPCAB on neuropsychiatric function within a frailer surgical patient population. 7 Important to note was the high frequency of antipsychotic use (approximately 24%) reported in this study. Current society guidelines recommend prescribing antipsychotics only for patients who have significant distress secondary to Off-pump CABG without aortic manipulation may have neurocognitive protective benefits.…”
Section: Delirium and Postoperative Cognitive Dysfunction (Pocd)mentioning
confidence: 69%
“…Although this assertion is well established, the effect of a stressor event on long‐term pre‐frail patients was not clear. A previous study with frail patients undergoing cardiac surgery has shown that the presence of preoperative frailty is associated with a twofold to threefold to fivefold higher risk of poor functional survival 1 year after of cardiac surgery 2,18 …”
Section: Discussionmentioning
confidence: 99%